Adaptive Optics for Industry and Medicine Proceedings of the 4th International Workshop, Münster, Germany, Oct. 19-24, 2003 - Wittrock, Ulrich (Springer Proceedings in Physics,, 2005)
This book treats the development and application of adaptive optics for industry and medicine. The contributions describe recently developed components for adaptive-optics systems such as deformable mirrors, wavefront sensors, and mirror drivers as well as complete adaptive optical systems and their applications in industry and medicine. Applications range from laser-beam forming and adaptive aberration correction for high-power lasers to retinal imaging in ophthalmology. The contributions are based on presentations made at the 4th International Workshop on Adaptive Optics in Industry and Medicine which took place in Münster, Germany, in October 2003. This highly successful series of workshops on adaptive optics started in 1997 and continues with the 5th workshop in Beijing in 2005.